Supporting children’s social play with peer-based intervention and instruction in four inclusive Swedish preschools - Gladh, Maria; Siljehag, Eva; Westling Allodi, Mara; Odom, Samuel L. (Frontiers in Education, 2022)
This multiple case study investigated a peer-based intervention and instruction (PBII) for social play, Play Time/Social Time (PT/ST), in four inclusive Swedish preschools. PT/ST contains 28 learning activities where children playfully practice six social skills with significance for social play and friendships. One teacher in each preschool was trained and instructed to implement PT/ST, two with coaching early in the implementation, and two without. At each preschool, one child with special educational needs (SEN) in social play (n=4) and one or two socially skilled peers (n=6) participated. The study aimed to explore how the teachers perceived the influence of PT/ST on social engagement and social play skills in the children with SEN, with/without coaching, and if PT/ST supported social play between the children with and without SEN. It also aimed to examine the feasibility of PT/ST and the influence on preschool inclusion quality in the preschools, with/without coaching. Observational assessments and video observations were used. The results indicate that PT/ST was beneficial for the children with SEN to engage in social play with peers and practice social skills, and for the preschool’s inclusion quality regarding involvement in peer interactions and guidance in play, both with/without coaching for the teachers. However, the coaching strengthened the intervention fidelity. Social play occurred between the children with and without SEN in activities where they seemed similarly attracted by the toys and play materials and when they all could engage in the play goals, tasks, and roles. For this, they sometimes needed instructions and encouragement from the teachers.